PENGARUH TOTAL QUALITY MANAGEMENT, SISTEM PENHARGAAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL - Nisa, Widya Choirun; Sapari, Sapari (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of Total Quality Management (TQM), appreciation system andorganization committment to the managerial performance. The research samples are 35 senior managers andstaffs at PT STAR Taman Remaja Surabaya. The sample collection has been done by using purposive samplingmethod. The data collection technique has been carried out by using primary data which has been gathered byissuing questionnaires to the respondents. The method in this research is quantitative whereas the analysistechnique has been done by using multiple linear regressions analysis. The result of the research shows that thecoefficient determination value is 66.3% and each of variable i.e. Total Quality Management (TQM), theappreciation system and the organization committment give significant influence to the managerialperformance. Meanwhile, 33.7% of the disclosure of firm value can be explained by other variables which are notincluded in the research model. It has been obtained from the result of model feasibility test that the model isfeasible to be used for further research. the result of hypothesis test shows that the influence of variables i.e. TotalQuality Management (TQM), the appreciation system and the organization committment give significant andpositive influence to the managerial performance.Keywords: Total Quality Management (TQM), appreciation, comitment, managerial performance.